1997
DOI: 10.1063/1.118544
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of texture at growth of titanium nitride films prepared by photon and ion beam assisted deposition

Abstract: The effect of the film thickness on the evolution of texture of polycrystalline titanium nitride films grown by photon and ion beam assisted deposition has been investigated. The layers were deposited in high-vacuum on (111)Si with the N-ion energy constant at 2 keV and the incident ion/titanium flux ratio constant at 0.66 ions/atom. X-ray pole figure measurements show that the biaxial {001} texture is changed to the biaxial {111} texture with an increase of the film thickness. The texture evolution is explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Results reveal that the lattice constant increased from 0.416 to 0.421 nm with increasing W content. Hones et al [12] investigated the electronic structure and mechanical properties from the chromium-tungsten nitride system and reported that the lattice parameter as a function of the tungsten content in [16,17]. In the present study, the B1 fcc structure of Cr 1 − x W x N y films (Fig.…”
Section: Microstructurementioning
confidence: 78%
“…Results reveal that the lattice constant increased from 0.416 to 0.421 nm with increasing W content. Hones et al [12] investigated the electronic structure and mechanical properties from the chromium-tungsten nitride system and reported that the lattice parameter as a function of the tungsten content in [16,17]. In the present study, the B1 fcc structure of Cr 1 − x W x N y films (Fig.…”
Section: Microstructurementioning
confidence: 78%
“…(i) The preferred orientations of films are decided by the lowest overall energy conditions between the strain and surface energies [18][19][20]. (ii) The preferred orientations of films depend on the atomic bombardment and mobility [21][22][23].…”
Section: Xrd Analysismentioning
confidence: 99%
“…4) It should be noted t h a t the evolution of the texture of the TiN crystallites on S i ( l l l ) is also depended on the film thickness [8].…”
Section: The Ion Beam Assisted Deposition Processmentioning
confidence: 99%
“…In summary, the results show t h a t the low energy ion assisted deposition is advantageous for preparing epita.xial GaN films. 6 S u m m a r y Three important effects during the IBAD of thin nitride films have been presented. The bia.xiaI "alignment of TiN on S i ( l l l ) films prepared by nitrogen ion b e a m assisted deposition a t room temperature was studied.…”
Section: The Ion Beam Assisted Deposition Processmentioning
confidence: 99%
See 1 more Smart Citation